Correlation of flow complexity parameter with aneurysm rupture status. (9th August 2018) - Hodis, Simona
Abstract: Ruptured aneurysms are known to have complex flow patterns and concentrated inflow jet, but a quantifiable measure for the degree of flow complexity in patient‐specific geometries has not been established. Previously, we proposed a flow complexity parameter that provides a quantitative description of the complexity of flow patterns through calculated curvature and torsion of the flow field. The purpose of the current study was to provide an analytic solution of the flow complexity parameter and assess a possible correlation with the rupture status of cerebral aneurysms by analyzing the parameter on five ruptured and five unruptured aneurysms from anterior communicating artery. We analyzed the flow complexity parameter in jet and non‐jet regions in order to measure the concentration of the jet flow and the complexity of the non‐jet flow. We found that on average, in a ruptured case the jet region is significantly less complex (4.5 times) than the jet region in an unruptured case, while the non‐jet region is significantly more complex (3.5 times) than the non‐jet region in an unruptured case. We also found a strong positive correlation of the non‐jet complexity with dome volume in ruptured cases, but no correlation of jet complexity with dome volume. These findings suggest that a ruptured aneurysm has more than 4 times more concentrated inflow jet and more than 3 times more complex flow patterns in non‐jet region than an unruptured aneurysm. This newly implemented kinematic parameter provides a measurable degree of complexity of flow patterns in cerebral aneurysms that can better assess aneurysm rupture risk. Abstract : The newly implemented kinematic parameter provides a measurable degree of complexity of flow patterns in cerebral aneurysms that can better assess aneurysm rupture risk. Using five ruptured and five unruptured aneurysms, we found that on average, a ruptured case has more than 4 times more concentrated inflow jet and more than 3 times more complex flow patterns in non‐jet region than an unruptured aneurysm. We also found a strong positive correlation of the non‐jet complexity with dome volume in ruptured cases.